2019
DOI: 10.1104/pp.19.00082
|View full text |Cite
|
Sign up to set email alerts
|

A Multiprotein Complex Regulates Interference-Sensitive Crossover Formation in Rice

Abstract: Complementation of osshoc1-2For the complementation test, the genomic sequence of OsSHOC1 containing 2505 bp upstream of the start codon, the coding region, and 131 bp downstream 232

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…Fluorescent in situ hybridization (FISH) assay was performed as described ( Cheng, 2013 ). The sequences of the centromere and 5 S rDNA FISH probes were designed and labeled as described ( Mizuno et al, 2006 ; Zhang et al, 2019 ). Images were captured with an Eclipse Ni-E microscope and NIS elements software (Nikon).…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescent in situ hybridization (FISH) assay was performed as described ( Cheng, 2013 ). The sequences of the centromere and 5 S rDNA FISH probes were designed and labeled as described ( Mizuno et al, 2006 ; Zhang et al, 2019 ). Images were captured with an Eclipse Ni-E microscope and NIS elements software (Nikon).…”
Section: Methodsmentioning
confidence: 99%
“…In rice (Oryza sativa), MutSg promotes formation of the obligate CO and is required for 78% to 90% of chiasmata (Luo et al, 2013;Zhang et al, 2014;Wang et al, 2016). In addition, a direct physical association between OsMSH4 and OsMSH5 as well as between OsMSH5 and HEI10 was demonstrated using yeast two-hybrid and pull-down assays (Zhang et al, 2014), as were interactions between OsMSH5 and replication protein A family members (OsRPA1a, OsRPA2b, OsRPA1c, and OsRPA2c; Wang et al, 2016) and OsSHOC1 (Zhang et al, 2019). In Arabidopsis and rice mutSg mutants, immunolocalization of the synaptonemal complex transverse filament proteins appeared normal, indicating a minimal effect on synapsis during prophase I (Higgins et al, 2004;Luo et al, 2013;Zhang et al, 2014).…”
mentioning
confidence: 98%
“…23 In Arabidopsis and rice, knock-out of SHOC1 can lead to a striking reduction in the number of meiotic crossovers. [24][25][26] In mice, it is demonstrated that Mzip2 knock-out male and female mice are sterile. Spermatogenesis in Mzip2 −/− mice arrests at zygotene stage, and there is no SC assembly and expression of MLH1 loci in the Mzip2 deficiency spermatocytes.…”
Section: Discussionmentioning
confidence: 99%